Peran Kompetensi Guru terhadap Problem Solving Siswa - Khaerul Anam; Gunawan Wiradharma; Nining Suryani; Raden Sudarwo (JOEAI:Journal of Education and Instruction, 2021)
This study aims to determine the effect of teacher competence from four dimensions, namely pedagogic competence, professional competence, personality competence, and social competence on students' problem solving abilities. This type of research is a survey type quantitative research. The samples in this study were fourth grade elementary school students taken from three schools in the districts of West Lombok and Central Lombok. Data collection methods in this study used tests, questionnaires, unstructured interviews and documentation. The data obtained were then analyzed by simple linear regression to determine the extent of the influence of teacher competence on student problem solving. The results of this study indicate that pedagogic competence and social competence of teachers have a significant influence on student problem solving, while professional competence and personality competence do not have a significant effect. In conclusion, the role of teacher competence, namely pedagogic competence and social competence, has a significant aspect on students' problem solving abilities, although this effect does not apply in all schools, and teacher pedagogic competence on student problem solving, but does not occur in one school only. Keywords: Teacher Competence, Problem Solving, Quantitative Survey